Pengaruh Lama Perebusan terhadap Kualitas Kimia dan Organoleptik Abon dari Bagian Dada dan Paha Ayam Petelur Afkir - Prasetyo, Eko; Patriadi Nuhriawangsa, Adi Magna; Swastike, Winny (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2012)
The aim of this study was to determine the effect of boiling time and muscle parts and the interaction of those two factors on chemical and organoleptic quality of abon of post laying hen. Poultry meat samples used were breast and thigh of post laying hens. The design used was Completely Randomized Design of Factorial Pattern 2 x 3. The first factor was boiling time (15, 30, 45 minutes) and the second was muscle parts (breast and thigh). Water content was tested by Gravimetric, fat content by Soxhlet extraction, protein content by Buret and quality of organoleptic included juicy,flavour and preference. Water and proteins content were affected (P <0.01) by boiling time and muscle parts. Flavor and preferences were not affected by boiling time and meat type. Juicy was affected (P <0.01) by muscle location. Breast meat with boiling 30 minutes and thigh meat with boiling 45 minutes have the best quality.Keywords: abon, breast, leg, boiling time, chemical quality, organoleptic.